When nutrition becomes artificial: A bioethical issue - Karaboue, Michele; Massaro, Michele; karaboue, karidia (Progress in Nutrition, 2023)
There is an inextricable link between nutrition in its various aspects and the general well-being of human beings. It is possible to draw up a guide for reflection as a proposal of bioethics to be applied to the reality of nutrition, starting from the analysis of human behavior. The focus is on the role of food for the human being from a bioethical point of view, highlighting the ethical value of nutrition and the psychological and socio-relational aspects associated with it. These aspects were then rejected in the context of quality of life and artificial nutrition in its various aspects.